PENGARUH PEMBERIAN EKSTRAK ETANOL BUNGA TELANG TERHADAP KADAR CRP (C-REACTIVE PROTEIN): Studi Eksperimental pada Tikus Putih Jantan Galur Wistar yang dipapar Asap Rokok - Kartika Aeni Zahroh; Eni Widayati (PT. Hasba Edukasi Mandiri, 2026)
Exposure to cigarette smoke contains toxic substances such as nicotine that can trigger oxidative stress, thereby stimulating the liver to produce C-reactive protein (CRP) as an indicator of systemic inflammation. Butterfly pea flower extract (Clitoria ternatea L.) contains anthocyanin compounds from the flavonoid group, which play a role in reducing CRP levels through anti-inflammatory mechanisms. This study aimed to determine the effect of ethanol extract of butterfly pea flower (Clitoria ternatea L.) on CRP levels in Wistar strain rats exposed to cigarette smoke. This was an experimental study using a post-test only control group design with a total sample of 30 rats divided randomly into five groups: Group 1 (normal control), Group 2 (negative control exposed to cigarette smoke), Group 3 (aspirin 9 mg/200 g BW), Group 4 (ethanol extract of butterfly pea flower 200 mg/200 g BW), and Group 5 (ethanol extract of butterfly pea flower 400 mg/200 g BW). The treatments were administered for 14 days, and on day 15 blood samples were collected to measure CRP levels using the ELISA method. Data analysis was performed using the One-Way ANOVA test followed by the Post Hoc LSD test. The mean CRP levels were 0.77 ng/mL in K0, 2.31 ng/mL in K(–), 0.94 ng/mL in P1, 1.00 ng/mL in P2, and 0.80 ng/mL in P3. These results indicate that the administration of butterfly pea flower ethanol extract reduced CRP levels compared to the negative control. The One-Way ANOVA test showed a significant difference (p < 0.05). Administration of ethanol extract of butterfly pea flower (Clitoria ternatea L.) affected CRP levels in Wistar rats exposed to cigarette smoke.